The Impact of Using E-Filing on Taxpayers is Reviewed from the Principle of Legal Certainty - Putri Yashila Rahimah Athifahputih; Rehnalemken Ginting (MultiTech Publisher, 2023)
E-Filing is a service for sending or submitting Annual Tax Returns (SPT) electronically for individuals or entities (Companies or Organizations) to the Directorate General of Taxes via online and real time internet communication channels which are referred to as ASP (Application Service Provider or Service Provider Application). By utilizing this technology, Taxpayers (WP) no longer need to print all report forms and wait for receipts manually. Therefore, this research aims to determine the implementation of E-Filing in terms of the principle of legal certainty and its impact on society. This research uses a qualitative approach that is in accordance with the concept and scope of the problem. The data and information needed are taken from facts and events that have occurred. The results of the research are first, research shows that the use of E-Filing in SPT reporting in Indonesia has adequate legal certainty. This is because the mechanism and implementation have been regulated in the Decree of the Director General of Taxes. The E-Filing concept also provides significant benefits for Taxpayers, such as faster, more cost-effective and efficient reporting. Second, the impact felt by society. Taxpayers are happy with the E-Filing system design which is neat and easy to understand, so that it can increase tax compliance in submitting Annual Tax Returns. Thus, the use of E-Filing in SPT reporting is expected to improve tax compliance and improve tax performance in Indonesia.